Corrections to “Secure Biometric Identification Using Orca Predators Algorithm With Deep Learning: Retinal Iris Image Analysis” - Louai A. Maghrabi; Mohammed Altwijri; Sami Saeed Binyamin; Fouad Shoie Alallah; Diaa Hamed; Mahmoud Ragab (IEEE Access)
Presents corrections to the paper, Corrections to “Secure Biometric Identification Using Orca Predators Algorithm With Deep Learning: Retinal Iris Image Analysis”.